Implementation of the Village Revenue and Expenditure Budget on Development in Bajur Village, Labuapi Sub-District, West Lombok District 2020-2023 - Rinda Azzahra; Muhammad Alwi; Siti Sriningsih (West Science Business and Management, 2024)
This study aims to determine the implementation of the Village Budget (APBDes) on development in Bajur Village, Labuapi District, West Lombok Regency in 2020-2023. This research is qualitative research. The subjects of this research were the government and the community in Bajur Village. Data collection techniques in this study were carried out by means of observation, interviews, documentation, and literature study. To ensure data validity, the author used triangulation including method triangulation, inter-researcher triangulation, data source triangulation, and theory triangulation. Data were analyzed using the Miles and Huberman model, namely data collection, data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the Village Revenue and Expenditure Budget (APBDes) for development in Bajur Village, Labuapi District, West Lombok Regency in 2020-2023 showed compliance with applicable regulations and provisions. Bajur Village has implemented the APBDes properly and accountably. This can be seen from several aspects, namely: (1) APBDes planning is carried out in a participatory manner by involving the community through deliberations at the dusun and village levels, (2) APBDes implementation is carried out based on the RKPDes and APBDes that have been approved. The village empowers the community in the implementation of village programs and activities, and uses local labor, (3) APBDes administration is carried out carefully, thoroughly, and consistently. The village uses the Siskeudes application to assist in recording, classifying, and reporting village financial transactions, (4) APBDes reporting is submitted in stages and accountable to interested parties, both the government above and the village community, (5) APBDes accountability is submitted to various related parties through the submission of APBDes realization reports and information media.